HUBUNGAN TINGKAT KEMANDIRIAN LANSIA DALAM MELAKUKAN AKTIVITAS SEHARI-HARI DENGAN TINGKAT KECEMASAN - Cahyono, Aris Dwi (Jurnal AKP, 2013)
Elderly was person who have ages more than 60 years old (WHO). Elderly was continued stage of a life process that will experienced of all an individual (Azizah,2011). Elderly will experience aging process. Aging process was tends to potentially decreased the degree of independence of the elderly in performing daily activities(Maryam, 2008). Decrease in the level of independence in the elderly can lead to anxiety (Herman, 2009). From the results of the survey encountered many elderly who have decreased levels of independence and anxiety. The purpose of this study was to determine the relationship of the level of independence of the elderly in performing daily activities with the level of anxiety.Research design used in this study is the Analytic Cross Sectional. The population in this study were all elderly in the village of Margomulyo Puncu totaling 123 elderly and in grab samples of 54 respondents. Research gauges the degree of independence of the elderly using questionnaires according to Katz index, whereas the level of anxiety using the questionnaire according to Hars. Analysis of the data in this study using Descriptive Analytics.The results showed that there is a relationship between the degree of independence of the elderly in performing daily activities with the level of anxiety in the hamlet village Margomulyo Puncu Puncu Kediri District in 2013The existence of a relationship between the degree of independence of the elderly with anxiety level, is influenced by factors of age and education. More severe in the elderly dependency perform daily activities, the more severe level of anxiety. So it is advisable for the elderly at the time of independence would decrease the level of physical training to maintain functional ability and social support to the elderly in order to avoid anxiety.Â Keywords: Elderly, Independence, Anxiety